2017
DOI: 10.1101/188664
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age-related differences in prestimulus subsequent memory effects assessed with event-related potentials

Abstract: Prestimulus subsequent memory effects (preSMEs) -differences in neural activity elicited by a task cue at encoding that are predictive of later memory performance -are thought to reflect differential engagement of preparatory processes that benefit episodic memory encoding. We investigated age differences in preSMEs indexed by differences in ERP amplitude just prior to the onset of a study item. Young and older adults incidentally encoded words for a subsequent memory test. Each study word was preceded by a ta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
15
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 93 publications
3
15
2
Order By: Relevance
“…The results from the different measures of the neuropsychological test battery are reported in Table 1. The pattern of age differences is essentially identical to our prior report (Koen et al, 2018), which is not surprising given the high degree of overlap between the samples (see Participants section of the Methods). There were significant effects of age, with older adults performing worse on tests assessing declarative memory, reasoning ability, category fluency, and processing speed.…”
Section: Neuropsychological Test Performancesupporting
confidence: 81%
“…The results from the different measures of the neuropsychological test battery are reported in Table 1. The pattern of age differences is essentially identical to our prior report (Koen et al, 2018), which is not surprising given the high degree of overlap between the samples (see Participants section of the Methods). There were significant effects of age, with older adults performing worse on tests assessing declarative memory, reasoning ability, category fluency, and processing speed.…”
Section: Neuropsychological Test Performancesupporting
confidence: 81%
“…In striking contrast to findings from prior fMRI studies employing intentional or semantically elaborative study tasks (e.g., Adcock et al, 2006;Park & Rugg, 2009;Addante et al, 2015;, here we identified exclusively negative pre-stimulus SMEs in both the cortex and the left hippocampus. The reasons for this striking divergence from prior findings are unclear, although part of the answer may lie in the plethora of procedural differences between the present and prior studies (as noted in the Introduction, a seemingly minor procedural variation can be sufficient to reverse the direction of electrophysiological measures of prestimulus SMEs; Koen et al, 2018). For example, to our knowledge, the present study is the first to use fMRI to examine pre-stimulus SMEs predictive of subsequent source, as opposed to item or associative, memory performance.…”
Section: Negative Pre-stimulus Smescontrasting
confidence: 67%
“…By contrast, an EEG study by Strunk & Duarte (2019) reported age-invariant effects in time-frequency measures of pre-stimulus neural activity elicited by pre-stimulus cues that signaled the modality of the upcoming study item. Contrary to the conclusions of Koen et al (2018), these authors proposed that older and young adults were equally capable of engaging pre-stimulus anticipatory processes that facilitate episodic encoding.…”
mentioning
confidence: 75%
See 2 more Smart Citations